Simulated response of the climate of eastern Africa to stratospheric aerosol intervention - Misiani, Herbert O.; Endris, Hussen S.; Opijah, Franklin J.; Ouma, Jully O.; Barasa, Betty N.; Tye, Mari R.; MacMartin, Douglas G. (Frontiers in Climate, 2025)
Eastern Africa is vulnerable to extreme climate events, including droughts and floods, which are expected to become more frequent and intense in the future. This paper evaluates the potential of solar radiation management (SRM) with stratospheric aerosol injection (SAI) to influence the projected climate, including extreme events, over the region. The study utilized climate simulation outputs from the Community Earth System Model version 2 with the Whole Atmosphere Community Climate Model (CESM2-WACCM6) to assess future climate changes under two scenarios: one without Solar Aerosol Injection (SAI) following the SSP2-4.5 emissions pathway, and another with SAI, based on the first set of simulations from the Assessing Responses and Impacts of Solar Climate Intervention on the Earth System with Stratospheric Aerosol Injection (ARISE-SAI) project. The analysis of model performance was conducted for the 1981–2010 period, while future changes were assessed over two climatological periods: the near-term (2035–2054) and the mid-term (2050–2069). Changes in extreme temperatures and rainfall events were evaluated using four extreme indices: two for temperature (WSDI and DTR) and two for rainfall (CDD and CWD). Additionally, the Standardized Precipitation-Evapotranspiration Index (SPEI) was used to assess changes in the frequency of extreme wet and dry events. In the historical period, there is good agreement between the observed and simulated data in representing the spatial distribution of temperature and rainfall over the region, despite the slight overestimation and underestimation by the model in some areas. The model effectively captures the seasonal cycles of rainfall and temperature over the cities of interest. Analysis of future projections indicates that temperatures are projected to rise consistently in the future under the SSP2-4.5 scenario. However, SAI produces a steady trend in the four cities, suggesting SAI’s potential to counteract warming in Eastern Africa. Rainfall is projected to increase in the equatorial region compared to the reference period, while other areas remain stable. ARISE-SAI shows higher increases in rainfall during the MAM season but lower increases during the JJAS and OND seasons compared to SSP2-4.5. Overall, the study’s findings suggest that SAI technology could have a clear effect in reducing temperatures in Eastern Africa, both in the near- and mid-term futures. However, its impact on rainfall varies by region and season, indicating that further simulations with a wider range of scenarios and analyses are required to assess the robustness of these results. The results of this study should be interpreted cautiously since they are specific to the approach of SAI applied, the modelling experiments employed, and the scenarios considered.